Tautological Expressions and the Affirmation of God’s Oneness in the Qur’an: A Stylistic and Theological Analysis - Marzuqi Marzuqi; Akhmad Muzakki (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2025)
This study investigates how the Qur’an employs tautological language to articulate and affirm the existence of God. The research aims to identify the structural patterns of tautology used in Qur’anic expressions about the divine and to reveal the theological meanings embedded within these stylistic choices. It addresses how repetition, synonymous diction, and emphatic linguistic forms contribute to constructing a coherent and powerful discourse on God’s oneness and ultimate authority. Using a qualitative design, this research applies a stylistic approach supported by library-based data collection. The primary data consist of Qur’anic verses related to God’s existence, examined through authoritative classical tafsir sources, including al-Kashshaf, Tafsir al-Tabari, and Tafsir al-Qurthubi. Analytical procedures cover diction analysis, sentence structure examination, and interpretive exploration of rhetorical meaning to uncover the semantic and stylistic functions of tautology in Qur’anic discourse. The findings reveal three dominant stylistic constructions: kalam khabar (informative statements), qashr (restrictive structures), and predicate–subject equivalence. These forms emphasize God’s absolute oneness, His all-encompassing power, and the certainty of the hereafter. Tautological structures serve as theological reinforcement, confronting pre-Islamic belief systems and affirming monotheism as the foundation of Islamic worldview.